Relationships between membrane lipids and ion transport in red blood cells of Dahl rats - Vokurková, Martina; Nováková, Olga; Dobesová, Zdenka; Kunes, Jaroslav; Zicha, Josef (Life sciences, 2005)
Distinct changes of membrane lipid content could contribute to the abnormalities of ion transport that take part in the development of salt hypertension in Dahl rats. The relationships between lipid content and particular ion transport systems were studied in red blood cells (RBC) of Dahl rats kept on low- and high-salt diets for 5 weeks since weaning. Dahl salt-sensitive (SS/Jr) rats on high-salt diet had increased blood pressure, levels of plasma triacylglycerols and total plasma cholesterol compared to salt-resistant (SR/Jr) rats. Furthermore, RBC of SS/Jr rats differed from SR/Jr ones by increased content of total membrane phospholipids, but membrane cholesterol was not changed significantly. SS/Jr rats had higher RBC intracellular Na+ (Na(i)+) content and enhanced bumetanide-sensitive Rb+ uptake. RBC membrane content of cholesterol and phospholipids correlated positively with RBC Na(i)+ content, with the activity of Na+-K+ pump and Na+-K+-2Cl- cotransport and also with Rb+ leak. The content of phosphatidylserines plus phosphatidylinositols was positively associated with RBC Na(i)+ content, with the activity of Na+-K+ pump and Na+-K+-2Cl- cotransport and with Rb+ leak. The content of sphingomyelins was positively related to Na+-K+-2Cl- cotransport activity and negatively to ouabain-sensitive Rb+-K+ exchange. We can conclude that observed relationships between ion transport and the membrane content of cholesterol and/or sphingomyelins, which are known to regulate membrane fluidity, might participate in the pathogenesis of salt hypertension in Dahl rats.
Keywords: sodík-draslík-chloridové symportéry; sodíko-draslíková ATPasa; Male; hypertenze; erytrocytární membrána; potkani inbrední Dahl; Cholesterol; Sodium-Potassium-Chloride Symporters; mužské pohlaví; Erythrocyte Membrane; Hypertension; Rats, Inbred Dahl; iontový transport; Membrane Lipids; Sodium Chloride, Dietary; krysa rodu Rattus; cholesterol; Animals; Ion Transport; Sodium-Potassium-Exchanging ATPase; zvířata; Rats; erytrocyty; Erythrocytes; kuchyňská sůl; membránové lipidy